PRELIMINARY STUDY: ANALYSIS OF SCIENCE LEARNING NEEDS ON HUMAN DIGESTIVE SYSTEM MATERIAL GRADE VIII SMP / MTS - Lusi, Dila Evi; Widiana, Rina; Maharani, Ade Dewi; Zuliarni, Zuliarni (Universitas PGRI Sumatera Barat, 2023)
The aim of this research is to analyze and describe the students' needs for biology learning resources used in the eighth-grade classroom at MTsS Qasratul Jannah. The instruments used in the study include interview questionnaires with teachers, student needs questionnaires, and book analysis. Based on the interview results, it was found that the school only uses one textbook and worksheets available in the market. Additionally, 0% of students have not met the Minimum Completion Criteria (KKM) in the material on the human digestive system. The student needs questionnaire revealed that 94.7% of students face difficulties in understanding the material on the human digestive system, and 42.1% of students prefer handout teaching materials. The book analysis revealed deficiencies in the teaching materials, as they do not cover efforts to maintain the health of the human digestive system, and do not include illustrations in each topic. Based on the analysis, supporting teaching materials are needed, such as handouts that align with the students' needs